Analisis Peningkatan Jumlah Transportasi Kota Surabaya Menggunakan Sistem Dinamik - Dea Puspita Anggraeni; Carissa Renatasari; Paulina April Romaito Pakpahan; Seftin Fitri Ana Wati (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the increase in transportation volume in Surabaya City using a dynamic system approach. A dynamic system is a modeling method used to understand and simulate the interactions between various components within the city's transportation system. These components include population growth, the increase in motor vehicles, road infrastructure, and existing government policies. In this study, the dynamic system is employed to model various scenarios of transportation growth. Computer simulations enable researchers to explore the impact of each scenario on different aspects such as traffic congestion, air pollution, and the quality of life of the residents. The simulation results indicate that without appropriate interventions, the increase in transportation volume will continue to rise along with population growth. This has the potential to worsen traffic conditions, increase air pollution emissions, and decrease the quality of life for residents in Surabaya City. This study also provides several policy recommendations that can be implemented by the Surabaya City government to manage transportation growth more sustainably. These recommendations include the development of more efficient and environmentally friendly public transportation, the improvement of road infrastructure quality, and the implementation of more effective traffic control policies. By adopting these policies, it is hoped that transportation growth can be better managed, minimizing its negative impacts on the environment and the community